2016
DOI: 10.1155/2016/2019212
|View full text |Cite
|
Sign up to set email alerts
|

Colocutaneous Fistula after Open Inguinal Hernia Repair

Abstract: The plug-and-patch technique is frequently used for the open repair of inguinal hernias; however, serious complications may arise on rare occasions. We present the case of a 69-year-old patient who presented with a colocutaneous fistula with the sigmoid colon 9 years after the repair of a left sliding inguinal hernia with the plug-and-patch technique. The patient underwent sigmoidectomy and excision of the fistulous track. He was discharged on postoperative day 5 and had an uneventful recovery. Although such c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 9 publications
(9 reference statements)
0
12
0
Order By: Relevance
“…Upon review of the literature, we have found seven cases of colocutaneous fistulas after open inguinal hernia repairs, presented below in Table 1. Six of these involved a left inguinal hernia and the sigmoid colon; five of the six utilized the plug and patch technique [1][2][3]6,11] and the remaining one employed the Lichtenstein technique [12]. Only one of the seven cases involved the cecum with plug and patch of a right inguinal hernia repair [5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Upon review of the literature, we have found seven cases of colocutaneous fistulas after open inguinal hernia repairs, presented below in Table 1. Six of these involved a left inguinal hernia and the sigmoid colon; five of the six utilized the plug and patch technique [1][2][3]6,11] and the remaining one employed the Lichtenstein technique [12]. Only one of the seven cases involved the cecum with plug and patch of a right inguinal hernia repair [5].…”
Section: Discussionmentioning
confidence: 99%
“…There are many plausible risk factors for mesh migration and/or fistula formation. These can be mechanical in nature, including inadequate initial anchoring, unsatisfactory placement of the mesh plug, direct contact between mesh and bowel, and type of hernia [1][2][3][4][5][6]8,11,12].…”
Section: Years Postoperativelymentioning
confidence: 99%
See 2 more Smart Citations
“…Different types of synthetic mesh can be used. Nevertheless, complications have been reported, such as infection [ 3 ], bowel perforation [ 4 ],colo-cutaneous fistula [ 5 , 6 ] and migration [ 7 ]. In this paper, we report a case of a mesh migration into the abdominal cavity that has been taken for a right colonic malignancy.…”
Section: Introductionmentioning
confidence: 99%